Alcohol Dimer is Requisite to Form an Alkyl Oxonium Ion in the Proton Transfer of a Strong (Photo)Acid to Alcohol. Issue 13 (28th January 2016) - Park, Sun‐Young; Lee, Young Min; Kwac, Kijeong; Jung, Yousung; Kwon, Oh‐Hoon
Abstract: Alcohols, the simplest amphiprotic organic compounds, can exhibit either acidic or basic behavior by donating or accepting a proton. In this study, proton dissociation of a model photoacid in solution is explored by using time‐resolved spectroscopy, revealing quantitatively for the first time that alcohol acts as a Brønsted base because of H‐bonded cluster formation to enhance the reactivity. The protonated alcohol cluster, the alkyl oxonium ion, can be regarded as a key reaction intermediate in the well‐established alcohol dehydration reaction. This finding signifies, as in water, the cooperativity of protic solvent molecules to facilitate nonaqueous acid–base reactions. Abstract : Dimer delights : The formation of an alkyl oxonium ion, a long‐proposed intermediate in alcohol dehydration, is studied by time‐resolved fluorescence quenching of a strong Brønsted photoacid. The collaboration of two alcohol molecules is critical to enhance the reactivity and extract the proton from the acid.